Thogoto Virus Lacking Interferon-Antagonistic Protein ML Is Strongly Attenuated in Newborn Mx1-Positive but Not Mx1-Negative Mice - Pichlmair, Andreas (American Society for Microbiology, 2004)
The Thogoto virus ML protein suppresses interferon synthesis in infected cells. Nevertheless, a virus mutant lacking ML remained highly pathogenic in standard laboratory mice. It was strongly attenuated, however, in mice carrying the interferon-responsive Mx1 gene found in wild mice, demonstrating that enhanced interferon synthesis is protective only if appropriate antiviral effector molecules are present. Our study shows that the virulence-enhancing effects of some viral interferon antagonists may escape detection in conventional animal models.